Please Call the Specialism: Using WeChat to Support Patient Care in China - Wang, Ding, Santosh Kale; O'Neill, Jacki (CHI 2020, 2020)
We examine how WeChat has been adopted to support nurse patient communication in an IVF clinic in China. In this setting, the biggest challenge to delivering high-quality patient centered care is the large number of patients. Nurses typically spend less than five minutes with each patient during clinical visits. To compensate for such minimal in-person consultation, nurse-facilitated patient groups were created on WeChat, to extend medical care and facilitate peer support. Through an ethnographic study, we examined how these groups fit into the clinic’s communication ecosystem, and the challenges they raise for nurse-facilitators who receive thousands of messages daily. We propose a set of design suggestions aiming to make the work of the nurse-facilitator easier and more effective. In highlighting the opportunities and challenges of using chat to extend care beyond the clinic, we contribute to a burgeoning discussion of how chat can support patient care in the Global South.